Coral Fishes in Coral Reef Waters of Sub District Maba, East Halmahera egency North Maluku Province - Ari Rondonuwu (Jurnal Ilmiah PLATAX, 2014)
This study aims to determine the distribution and abundance of reef fish in coral reef waters of Sub District Maba and was conducted at 10 stations. Data were collected by conducting visual census on the 50-meter transect line at 5 meters depth. In addition to revealing the number of species and abundance of coral fishes, data were analyzed to determine the diversity index (Shannon-Wiener). Based on field observations, most of the reef fishes  found in the Sub-district of Maba surrounding waters are being categorized to have less potential category (50%);  fair potential (41.67%); potential (8:33%); and  there is no population being classified in very potential category. Several locations have the potential reef fish condition were Jara-jara Cape, Gee Island, and Para-para Island.  Based on the existence of the target species population, in term of species richness and abundance, it is assumed that largely dominated by the target fish species that has low economic value. On the other hand target fish that has high economic value only consists of few species such as grouper, jacks, sweetlips, and snappers.   Keywords : coral fishes,  coral reef, sub district maba ABSTRAK Penelitian ini bertujuan untuk mengetahui distribusi dan kelimpahan ikan karang di perairan terumbu karang Kecamatan Maba. Penelitian dilakukan di 10 lokasi. Pengambilan data dilakukan dengan metode sensus visual pada transek garis sepanjang 50 meter, kedalaman 5 meter. Selain mengungkapkan jumlah spesies dan kelimpahan individu, analisis data diarahkan untuk mengetahui indeks keanekeragaman (Shannon-Wiener).  Berdasarkan hasil pengamatan, sebagian besar sumberdaya ikan karang di wilayah Kecamatan Maba, telah masuk dalam kategori kurang potensial (50 %); cukup potensial (41,67 %); potensial (8.33%); dan tidak ada yang tergolong dalam kategori sangat potensial.  Lokasi-lokasi yang memiliki kondisi ikan karang yang potensial,  Tanjung Jara-jara, Pulau Gee, dan Pulau  Para-para. Keberadaan populasi spesies target, baik kekayaan spesies maupun kelimpahan individu, ternyata sebagian besar didominasi oleh jenis ikan target yang bernilai ekonomi/pasar rendah.  Beberapa jenis ikan yang memiliki nilai ekonimis penting ditemukan  seperti, kerapu, Sweetlips (bibir manis), Bobara, dan kakap. Keywords : coral fishes,  coral reef, sub district maba